2017
DOI: 10.5414/cn109049
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic uremic syndrome complicated by Clostridium septicum bacteremia and new-onset type 1 diabetes mellitus. Report of a case

Abstract: We report the unusual case of a 5-year-old male hospitalized for management of diabetic ketoacidosis (DKA) and new-onset type 1 diabetes mellitus (T1DM) who developed acute renal injury secondary to hemolytic uremic syndrome (HUS). He was diagnosed with Shiga toxin-producing entero-hemorrhagic Escherichia coli (EHEC) 0157:H7-positive HUS 48 hours after being diagnosed with new-onset T1DM/DKA. His hospital course was complicated by Clostridium septicum sepsis with colonic perforation. This patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…An onset of complement deficiency, pneumococcal infection, abnormal metabolism of cobalamin, and so on can lead to atypical hemolytic uremic syndrome (aHUS), which is related to genetic mutations and has a distinct pathophysiology. [ 3 , 6 , 7 ] So far, only a few cases of HUS have been triggered by a metabolic disease, such as diabetes mellitus [ 8 , 9 ] and metabolic disorder of cobalamin. [ 10 , 11 ] Recently, Adrovic et al described a case of a 6-year-old girl with CblC disorder, who was found to have a homozygous mutation in exon 4 of MMACHC, c. 484G >T. [ 11 ] Although the serum level of VitB12 was normal in the patient, the bone marrow showed an obvious degeneration, so we highly suspected that it was caused by metabolic abnormalities of cobalamin.…”
Section: Discussionmentioning
confidence: 99%
“…An onset of complement deficiency, pneumococcal infection, abnormal metabolism of cobalamin, and so on can lead to atypical hemolytic uremic syndrome (aHUS), which is related to genetic mutations and has a distinct pathophysiology. [ 3 , 6 , 7 ] So far, only a few cases of HUS have been triggered by a metabolic disease, such as diabetes mellitus [ 8 , 9 ] and metabolic disorder of cobalamin. [ 10 , 11 ] Recently, Adrovic et al described a case of a 6-year-old girl with CblC disorder, who was found to have a homozygous mutation in exon 4 of MMACHC, c. 484G >T. [ 11 ] Although the serum level of VitB12 was normal in the patient, the bone marrow showed an obvious degeneration, so we highly suspected that it was caused by metabolic abnormalities of cobalamin.…”
Section: Discussionmentioning
confidence: 99%
“…While few studies have directly linked the presence of a Clostridium infection to initiation of T1DM [104,105], a very large number of studies have implicated dysregulation in the number and types of gut Clostridia. In particular, Bifidobacteria, Bacteroides, and Lactobacilli all decrease significantly, while the number of Clostridia increases and is directly correlated with the degree of glucose dysregulation observed in the patient [26,37,[106][107][108][109][110][111].…”
Section: Relationship Of the Experimental Findings To Previous Resultsmentioning
confidence: 99%
“…They discovered differences in microbial population dynamics in animals with kidney disease, such as increased alpha diversity, relative decreases in Lachnospiraceae and Lactobacillus , and increases in some Clostridia and opportunistic taxa. Although few studies have directly linked Clostridium infection to type 1 diabetes mellitus (T1DM) initiation [ 36 , 37 ], many studies have suggested that disturbance of Clostridia is related to glucose dysregulation in patients [ 38 - 44 ]. Our study is among the few to explore the abundance of Clostridia at the class level in DN.…”
Section: Discussionmentioning
confidence: 99%